Serious Game Development for Color and Object Name Recognition in Early Childhood Education (Case Study: TKK Mitra) - Ferdian Aditya Pratama; Riana Magdalena; Stefani Prima Dias; Davin Jeremiah Alamsyah (SISFORMA, 2020)
The concept of playing and learning in the classroom has begun to change from playing using physical toys to playing using a computer such as games. The use of serious games as a learning media can help the improvement of dopamine hormones in human body, which is responsible for bringing pleasure and joy to our mind. When that hormone is triggered, the children will be easier to understand the information provided through the game. TKK Mitra has several problems, such as (1) The old computer with a low spec that they had, so it would be difficult for them to download or to install the new game. (2) The lack of games that can be used for teaching the children, so they often get bored quickly. The purpose of this research is to design an educational PC game. The result of this research is an education game for color and object recognition in English for early childhood education.